Analisis Kelayakan Usahatani Jamur Tiram (pleurotus ostreatus) Kasus: Petani Jamur Tiram di Desa Peguyangan Kaja Kecamatan Denpasar Utara - IDA BAGUS SAHADEWA; RATNA KOMALA DEWI; IDA AYU LISTIA DEWI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2019)
Analysis of Oyster Mushroom (pleurotusostreatus)(The Case of Oyster Mushroom Farmers in Peguyangan KajaVillage,North Denpasar Sub-District)The development of oyster mushrooms (pleurotusostreatus) is enough to encouragemushroom farming in Indonesia. The same thing was done by the farmers ofPeguyanganKaja Village, North Denpasar Sub-District, who were involved in oystermushroom farming. This research was conducted in August 2017 through December2017. The purpose of this study was to determine the feasibility of oyster mushroombusiness, analyzed using Net Present Value (NPV) investment criteria, Net benefit costratio (Net B / C), Internal rate of return (IRR), Payback Period (PBP), and Sensitivityanalysis and knowing the constraints experienced by farmers in cultivating oystermushrooms.Based on the research and the results of the analysis that has been done, the followingconclusion can be arrived at. Oyster Mushroom Farming with a capacity of 1.000,2.500, 3.000, 5.000 and 6.000 baglogs worthy of being farmed with an interest rate of12%, this is aimed at NPV> 0 (positive), Net B / C> 0 (positive), IRR> i that is 12%,and PP <Economic age of mushroom media (5 years) and, sensitivity analysis based onthe three sensitivity analyses, oyster mushroom farming at media mushroom capacity5,000 baglogs is not sensitive to, increases in operational costs, decreases in productionquantity and decreases the selling price of 10%. Constraints faced in the cultivation ofoyster mushrooms in the village of PeguyanganKaja, which is lowland, are that it isdifficult to obtain a level of humidity between 80% and 100%, which of course is easierto do if it is in the highland.